A Preliminary Research on Load Calculation Method of Stratified Air Conditioning System with Low-sidewall Air Inlets and Middle-height Air Outlets in Large Space Building. (2017) - Huang, Chen; Yue, Jing; Bai, Tianyu; Lv, Liugen; Zhang, Qianru; Chen, Jianchang
Abstract: In the current design manual, there is only the traditional load calculation method of the stratified air conditioning system with air jets, which is not applicable to calculate the load of the stratified air conditioning system with low-sidewall air inlets and middle-height air outlets. In this paper, a reduced-scale model chamber was used to investigate such topic. On the basis of traditional load composition and the previous studies of the research group, we finally got the new method. We respectively calculated the load in seven different conditions. The experimental result shows that: the load deviations between the traditional method and the experimental method ranges from -11.3% to -23.4%, and the maximum deviation was greater than 20%. But the range of load deviations between the new method and the experimental method was from -3.32% to 5.85%, and the maximum deviation was less than 6%.